Embryological Basis and Clinical Correlation of the Rare Congenital Anomaly of the Human Gall Bladder: - “The Diverticulum” - A Morphological Study - Jaba Rajguru; Shilpi Jain; Satyam Khare; Ratna R Fulzele; Rashmi Ghai (Journal of Clinical and Diagnostic Research, 2013)
Background: Diverticulum of the human gall bladder is an important but distinct anatomical entity with significant clinical implications. It is one of the rarest congenital anomalies of the gall bladder being rarely discussed in literature. This article details the morphology of the diverticula found, along with the embryological basis and clinical significance of this important anatomical and clinical entity. Aim: To study the diverticula found, with respect to their morphology, and ascertain whether they were of congenital or acquired variety. Setting and Designs: The present study is a retrospective study carried on hundred cadavers during undergraduate dissection, in the Department of Anatomy, Jawaharlal Nehru Medical College, Sawangi (Meghe), Wardha, and Department of Anatomy, Subharti Medical College , Meerut during a four year period i.e. 2008-2012 after obtaining necessary permission from institutional ethical committee. Material and Methods: Hundred gall bladder specimens collected from 10% formalin fixed cadavers were studied in detail with regard to their number, position, shapes dimensions and histology. Results: Nine, congenital (true) diverticula were found in one hundred gall bladder specimens. The diverticula were of various shapes and dimensions. They formed pouches on the luminal surface of the gall bladder. Diagnosis of congenital diverticulum was confirmed by histology. Conclusion: In this cadaveric study, solitary diverticulum was found in nine (9%) specimens out of one hundred specimens. Association of diverticulum with non-specific prolonged ailments, acalculus cholecystitis, cholecystitis and cholelithiasis, recurrent cholangitis and carcinoma of gallbladder has been reported in literature. This important anatomical as well as clinical entity poses challenges for radiologists and laparoscopic surgeons during interventional procedures and also should be differentiated from other types of congenital anomalies and pathological states of gall bladder.